A critical comparison of lanthanide based upconversion nanoparticles to fluorescent proteins, semiconductor quantum dots, and carbon dots for use in optical sensing and imaging. (28th March 2019) - Himmelstoß, Sandy F; Hirsch, Thomas
Abstract: The right choice of a fluorescent probe is essential for successful luminescence imaging and sensing and especially concerning in vivo and in vitro applications, the development of new classes have gained more and more attention in the last years. One of the most promising class are upconversion nanoparticles (UCNPs)—inorganic nanocrystals capable to convert near-infrared light in high energy radiation. In this review we will compare UCNPs with other fluorescent probes in terms of (a) the optical properties of the probes, such as their brightness, photostability and excitation wavelength; (b) their chemical properties such as the dispersibility, stability under experimental or physiological conditions, availability of chemical modification strategies for labelling; and (c) the potential toxicity and biocompatibility of the probe. Thereby we want to provide a better understanding of the advantages and drawbacks of UCNPs and address future challenges in the design of the nanocrystals.